Interpretation of Positive Reactions to Heaf Tuberculin Test in London Schoolchildren. Issue 5801 (11th March 1972) - Galbraith, N. S.; Hanson, Audrey; Shoulman, R.; Andrews, D. W.; Lee, D. B.
Abstract : A study of 289 children aged 12-14 years found to be Heaf test positive at routine testing was made to determine the likely cause of the positive tests. Only 12% of children grade 1 Heaf positive were likely to have had a previous infection with Mycobacterium tuberculosis, 49% were likely to have had infections with atypical mycobacteria, and in 39% no cause for the positive Heaf test was found. The positive Heaf test seems to us to be too sensitive. Both a negative and grade 1 positive should be regarded as not significant and these children given B.C.G. vaccine. Heaf grades 2, 3, and 4 should be regarded as significant and the children investigated for M. tuberculosis infection.